2020
DOI: 10.21203/rs.3.rs-28123/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Mental Health Problems in Formal and Informal Caregivers of Patients with Alzheimer's Disease

Abstract: Background: Caring for a person with Alzheimer's disease (AD) is associated with significant mental burden e.g., depression and anxiety, and difficulties with social, familial, and professional functioning. To date, few studies have examined variables which would allow for a comprehensive and detailed study of the relationship between personal resources and caregiver health status, with a majority of studies focusing on factors that contribute to increased caregiver's burden. Moreover, the available evidence f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It has been reported that depressive symptoms were more common among dementia caregivers than other caregivers [32]. Furthermore, worsening of dementia symptoms, especially BPSD, has a profound physical and psychological impact and increases depressive and anxiety symptoms among both formal and informal caregivers [33][34][35]. In this study, worsening of dementia symptoms was commonly reported (by 32.1% of participants) along with deterioration of cognitive function (89.1%) and deterioration of BPSD (38.3%).…”
Section: Discussion/conclusionmentioning
confidence: 53%
“…It has been reported that depressive symptoms were more common among dementia caregivers than other caregivers [32]. Furthermore, worsening of dementia symptoms, especially BPSD, has a profound physical and psychological impact and increases depressive and anxiety symptoms among both formal and informal caregivers [33][34][35]. In this study, worsening of dementia symptoms was commonly reported (by 32.1% of participants) along with deterioration of cognitive function (89.1%) and deterioration of BPSD (38.3%).…”
Section: Discussion/conclusionmentioning
confidence: 53%
“…The main predictors of caregivers' burden previously investigated have focused on financial difficulties, interpersonal relationships, concerns about treatment, and patients engaging in risk or harming behaviors (e.g., drinking, self‐harm, taking drugs) (Stomski and Morrison, 2019). Other studies showed that a low sense of comprehensibility and self‐efficacy (Sołtys & Tyburski, 2020), perceived stigma, and high levels of distress (Rafiq & Sadiq, 2019) can impact caregivers' mental health. Our findings complement previous studies by showing that the emotional representation of the psychiatric condition is a strong predictor of caregivers' burden.…”
Section: Discussionmentioning
confidence: 99%
“…Caregiver burden (Gérain & Zech, 2019; Liu et al, 2020; Sołtys & Tyburski, 2020; Tsai et al, 2021) is a concept that refers to the physical, emotional, and mental exhaustion or depersonalization a caregiver can experience (Gérain & Zech, 2019; Thompson et al, 2014) and it has been shown to have a negative impact on both the caregiver and the patient (Oruche et al, 2012). Caregivers' gender (i.e., female), educational level, professional status, financial difficulties, number of hours spent caregiving, and other psychosocial aspects (e.g., depression and anxiety levels, coping mechanisms, social isolation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Dementia care in Greece, similar to most European countries, is primarily provided at home by informal or unpaid caregivers (CGs) (mostly first-degree relatives) (Petmesidou, 2014). Dementia caregiving can be an extremely demanding and burdensome responsibility with significant repercussions to the quality of life (QoL) of the informal GCs of people with dementia (PwD) (Collins & Kishita, 2020; Sołtys & Tyburski, 2020). QoL is a multidimensional construct incorporating physical and psychological health, social relationships, personal beliefs and relationship with the environment, and therefore, it can provide an indicator of the overall impact of caregiving on the CG (WHO, 1998).…”
Section: Introductionmentioning
confidence: 99%